THE EFFECT OF ADDITION PAPAIN ON FEEDOF GROWTH AND SURVIVAL RATE OFVANNAMEI SHRIMP (Litopenaeus vannamei) IN AQUAPONIC RESIRCULATION SYSTEMS - Amriyani, Dessy; Pamukas, Niken Ayu; Putra, Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The aim of the study was to determine the optimal dose of papain in feed to increase growth and survival rate of vannamei shrimp (Litopenaeus vannamei)in aquaponic recirculation systems. Culture vessel in the form of tarp of 50 x 50 x 50 centimeters of 12 tarp with stocking density of 20 shrimp/m3. This research was using experimental method by completely random design (RAL) one factor with four treatments and three replications, the treatments were by giving papain in feed with different dose. The treatments were : P0= without papain, P1= 3 % , P2= 3,3 %, P3= 3,6% . The results showed that the addition of papain in feed with different dose, showed highly effect (P<0.05) on the total weight, specific growth rate, and survival rate. The best growth rates was found in treatment P1 with total weight: 0.53±0.04gram, specific growth rate: 0.92±0.01 % per day, and survival rate: 78.33±7.63%. Keywords: Vanname shrimp, Papain,Growth